A TRAP THAT TRAPS HEAVY IMPURITIES IN COTTON - Rayimjonov Mirzavali Botirali o’g’li; Pirnazarov Abdurasul Umataliyevich; Muradov Rustam Muradovich (Galaxy International Interdisciplinary Research Journal, 2023)
The iron sheets in the pocket of the device that catches heavy objects open automatically when the load is lowered with the help of an electromagnetic spring and sensors. The seeded cotton goes directly to the working return surface, which prevents damage to the seeded cotton and separates the accumulated part of the cotton.